Modeling and Mining Ubiquitous Social Media International Workshops MSM 2011, Boston, MA, USA, October 9, 2011, and MUSE 2011, Athens, Greece, September 5, 2011, Revised Selected Papers - Atzmueller, Martin.; Atzmueller, Martin.; Chin, Alvin.; Chin, Alvin.; Helic, Denis.; Helic, Denis.; Hotho, Andreas.; Hotho, Andreas. (Lecture Notes in Artificial Intelligence ;, 2012)
This book constitutes the joint thoroughly refereed post-proceedings of the Second International Workshop on Modeling Social Media, MSM 2011, held in Boston, MA, USA, in October 2011, and the Second International Workshop on Mining Ubiquitous and Social Environments, MUSE 2011, held in Athens, Greece, in September 2011. The 9 full papers included in the book are revised and significantly extended versions of papers submitted to the workshops. They cover a wide range of topics organized in three main themes: communities and networks in ubiquitous social media; mining approaches; and issues of user modeling, privacy and security.